На родине П. И. Чайковского: фотокнига / авторы-составители: О. Ф. Прудникова, Т. А. Поздеева - Прудникова О. Ф. (Удмуртия, 1990)
Экземпляры: ф.1 (1990) / Инвентарный номер: 31032 / Цена: / Сис.шифр: 85.31(2Рос.Удм) / Авт.знак: Н 12 / ГРНТИ: 18.41.91 / ББК: 85.313(2)1-8